Extension of shelf life of tuberose flowers using a combination of gamma irradiation and generally regarded as safe (GRAS) preservatives and assessment of antimicrobial potency of senesced flowers. Issue 2 (4th March 2017) - Ghosh, Probir Kumar; Bhattacharjee, Paramita; Das, Satadal
ABSTRACT: Tuberose cut flowers, available as loose flowers, were treated with gamma (γ) irradiation and generally regarded as safe (GRAS) preservative solutions for extension of shelf life. The flowers were packaged in low-density polyethylene bags, heat sealed and stored at 23 ± 2°C, 80% relative humidity (RH) and 4 ± 1°C, 40% RH, respectively. The flowers stored at these two temperature regimes were subjected to sensory evaluation and biochemical analyses. From these assessments, the longest shelf life of tuberose flowers was found to be 8 days at 23 ± 2°C, 80% RH (compared to 4 days for control) and 24 days at 4 ± 1°C, 40% RH (compared to 8 days for control) using combination treatment of low dose γ-irradiation (0.02 kGy) and preservative solutions (4% sucrose and 0.02% CaCl2 ). Ethanolic extract of tuberose flowers of the most shelf stable set (stored at 4 ± 1°C), i.e. at the end of 24 days, showed antimicrobial potency against the common skin pathogen Staphylococcus aureus (ATCC 25923 and MDR strains), suggesting utility of the senesced tuberose flowers for therapeutic applications. This preservation technique would promote export of tuberose flowers by extension of their shelf lives and allow utilization of these flowers, post senescence.